Emulsion centrifugal spinning for production of 3D drug releasing nanofibres with core/shell structure. Issue 3 (4th January 2017) - Buzgo, Matej; Rampichova, Michala; Vocetkova, Karolina; Sovkova, Vera; Lukasova, Vera; Doupnik, Miroslav; Mickova, Andrea; Rustichelli, Franco; Amler, Evzen
Abstract : Herein we describe the core/shell centrifugal spinning process to deliver susceptible bioactive molecules. Abstract : Herein we describe the core/shell centrifugal spinning process to deliver susceptible bioactive molecules. The fibres are produced from water-in-oil (W/O) emulsion, where poly-ε-caprolactone (PCL) dissolved in chloroform serves as the continuous phase and Pluronic F-68 (PF-68) dissolved in ethanol serves as the droplet phase. The successful core/shell fibre formation and discontinuous morphology of the core was identified by confocal microscopy. Encapsulation of a model enzyme resulted in protection of enzymatic activity and release during the first 7 days. The feasibility for tissue engineering applications was demonstrated by the incorporation of platelet lyophilisates as a source of growth factors. The cultivation of 3T3 fibroblasts and MG63 osteoblasts resulted in improved metabolic activity and fostered proliferation. Results of the study indicate that the proposed scaffold combines the 3D structure of scaffolds produced by centrifugal spinning with the drug delivery of growth factors.